The effects of N-acetylcysteine supplement on metabolic parameters in women with polycystic ovary syndrome: a systematic review and meta-analysis - Liu, Jiajun; Su, Haodong; Jin, Xueshan; Wang, Lan; Huang, Jieming (Frontiers in Nutrition, 2023)
Polycystic ovary syndrome (PCOS) is a common endocrine disease, often accompanied by metabolic disorders. Metformin, as an insulin sensitizer, is widely used to improve the metabolic function of PCOS, but may have gastrointestinal side effects. Emerging evidence suggests that Nacetylcysteine (NAC) improves metabolic parameters in PCOS and may be a potential alternative to metformin. Methods: We searched four online databases, PubMed, Embase, Web of Science, and Cochrane Library, from inception to April 1, 2023. The I² statistic and Cochrane's Q test were employed to determine heterogeneity between studies, with an I² value >50% or P < 0.1 considered significant. The data were expressed as standardized mean differences and corresponding 95% confidence intervals.Results: A total of 11 randomized controlled trials were included in the final analysis, including 869 women with PCOS. The results showed that NAC caused more changes in body mass index (SMD: -0.16, 95% CI: -0.40 to 0.08), body weight (SMD: -0.25, 95% CI: -0.50 to 0.00), fasting insulin (SMD: -0.24, 95% CI: -0.53 to 0.06), ratio of fasting blood glucose to fasting insulin (SMD: 0.38, 95% CI: -0.33 to 1.08), total cholesterol (SMD: -0.11, 95% CI: -0.39 to 0.17), triglycerides (SMD: -0.18, 95% CI: -0.63 to 0.28), and low-density lipoprotein (SMD: -0.09, 95% CI: -0.51 to 0.33) compared with metformin. Compared with metformin or placebo, NAC significantly reduced fasting blood-glucose levels (SMD: -0.23, 95% CI: -0.43 to -0.04; SMD: -0.54, 95% CI: -1.03 to -0.05, respectively). In addition, NAC significantly reduced total cholesterol (SMD: -0.74, 95% CI: -1.37 to -0.12), and this effect was observed when NAC was compared with placebo. However, NAC reduced HDL levels in women with PCOS compared with metformin (SMD: -0.14, 95% CI: -0.42 to 0.14).This study suggests that NAC is effective in improving metabolic parameters in PCOS and may be a promising nutritional supplement for the treatment of PCOS.